Use of crescentia alata and guazuma ulmifolia fruits in lamb feeding in subtropical region of Guerrero, Mexico. - Rojas Hernández, Saúl; Olivares Pérez, Jaime; Gutiérrez Segura, Isidro; Jiménez Guillén, Régulo; León López, Fortino; Córdova Izquierdo, Alejandro (Revista Científica de la Facultad de Ciencias Veterinarias, 2013)
Ver resumen pdf.